2011
DOI: 10.1155/2011/670581
|View full text |Cite
|
Sign up to set email alerts
|

Acral Lentiginous Melanoma: A Case Control Study and Guidelines Update

Abstract: Background. Malignant melanoma incidence is increasing dramatically. We report herein a case of the rarest acral lentiginous type. Case Report. A 58-year-old man presented with a melanoma resembling lesion over the sole of his right foot, measuring 15–20 mm in diameter. An excisional biopsy with a narrow (2 mm) margin of surrounding skin was obtained. Histological findings were consistent with a diagnosis of acral lentiginous melanoma. Sentinel lymph node biopsy was also performed and micrometastases were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
2
0
7
Order By: Relevance
“…Le MM se divise en 4 types histologiques (selon la classification de l'OMS 2006) rapportés ici par ordre de fréquence décroissante: le mélanome à extension superficielle (SSM), le mélanome nodulaire(NM), le mélanome lentigo malin(LMM) et le mélanome acrolentigineux(ALM) [5,6].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Le MM se divise en 4 types histologiques (selon la classification de l'OMS 2006) rapportés ici par ordre de fréquence décroissante: le mélanome à extension superficielle (SSM), le mélanome nodulaire(NM), le mélanome lentigo malin(LMM) et le mélanome acrolentigineux(ALM) [5,6].…”
Section: Discussionunclassified
“…Le mélanome acrolentigineux (ALM) ou mélanome acral (MA) touche la peau palmo-plantaire et sous-unguéale; Reed fût le premier à le décrire en 1976 comme type de MM [6].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…One of the problems with SLNB of lower extremities is the presence of pelvic SLNs. Kaoutzanis et al showed 11 of 82 cases with tumour on lower extremities had SLNs on the pelvic region and underwent SLNB [60]. They also showed that 19 of 82 cases (24%) had positive SLNs and all the positive SLNs were located in the inguinal region.…”
Section: Sentinel Lymph Node Biopsy On Lower Extremitiesmentioning
confidence: 99%
“…3 According to some of the reports, ALM on the sole has a worse prognosis than other areas of the body, however the tumor thickness has a greater impact on prognosis than anatomical location. 4 The prognosis of lesions on the sole may be worse due to the fact that they may be noticed lately.…”
mentioning
confidence: 99%